Integrated weed management strategies with cereal rye mulch in processing vegetable legumes. (27th August 2020) - Korres, Nicholas E.; Hausman, Nicholas; Moody, James L.; Kitis, Yasin E.; Williams, Martin M.
Abstract: Little is known about the potential benefits of cereal rye ( Secale cereale L.) in combination with various weed management tactics in processing vegetable legume crops such as edamame, lima bean, and snap bean. Field experiments were conducted over 3 yr to determine the extent to which early‐terminated rye (ETR) and integrated weed management (IWM) tactics, including pre‐ and post‐emergence herbicides with (augmented) or without (standard) hand weeding, suppress weed density and biomass. Possible drawbacks on crop establishment and yield were also investigated. Early‐terminated rye (cereal rye terminated 4 wk before vegetable crops planting; i.e., Feekes growth stage 8.00 to 9.00) reduced total weed biomass 53 and 73% compared with stale seedbed (SSB) in edamame and snap bean, respectively. In contrast, total weed density and biomass were increased by 67 and 39%, respectively, in lima bean under ETR compared with SSB treatment. Early‐terminated rye did not influence edamame establishment or yield; however, snap and lima beans had reduced yield. Soil nitrate‐nitrogen 4 wk after planting was negatively correlated with soil moisture in all vegetable legume crops tested. The application of pre‐ and post‐emergence herbicides, particularly when followed by hand weeding, reduced weed density and biomass and improved yield in all crops, except snap bean, compared with weedy plots. Results show that ETR can serve as an important component of IWM in edamame.